2001
DOI: 10.1016/s0016-5085(01)82229-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic balloon dilatation of Crohn's strictures

Abstract: Aim: To evaluate the safety and long-term efficacy of per-endoscopic hydrostatic balloon dilatation in a retrospective series of patients with Crohn's disease. Methods: Thirty-eight patients had balloon dilatation for intestinal symptomatic strictures which were located as follows: ileo-colonic (26) or colocolic (2) anastomosis, colon (4), ileum (3), proximal jejunum (1) and ileocaecal valve (5); three patients had two strictures accessible to dilatation. The mean length of the strictures was 2.1 cm (s.d., 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 13 publications
1
41
0
4
Order By: Relevance
“…At the moment, it is difficult to define the relapse risk after endoscopic balloon dilatation, as the published studies [8,[17][18][19] are based on very different follow-up periods, and often do not represent structured prospective longterm studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the moment, it is difficult to define the relapse risk after endoscopic balloon dilatation, as the published studies [8,[17][18][19] are based on very different follow-up periods, and often do not represent structured prospective longterm studies.…”
Section: Discussionmentioning
confidence: 99%
“…Valid long-term studies of 5 years or more, which would permit a statement regarding recurrence of strictures and a better comparison with surgical techniques [3,4] , are available so far only in casuistic form and with limited numbers [8,[17][18][19] . We report on our own prospective 10-year long-term study of endoscopic balloon dilatation of strictures in Crohn's disease using a relatively thin balloon (18 mm) and additional treatment with prednisolone.…”
Section: Introductionmentioning
confidence: 99%
“…[161][162][163][164][165][166] Two further case series did however report haemorrhage associated with dilation of ileal or colonic strictures in 1/20 (5%) 167 and 1/38 (2.6%) patients. 168 One study included dilation of malignant strictures and encountered no haemorrhagic complication in 94 cases (68 malignant and 26 anastomotic strictures). 169 In a RCT of pneumatic dilatation versus laparoscopic myotomy for achalasia there were no reported haemorrhages but 8/108 (9.5%) patients experienced perforation during the treatment course.…”
Section: Dilatationmentioning
confidence: 99%
“…Even with these multiple dilatations the long-term success rates are imperfect. At 1 year Sabate et al 7 reported only a 64% symptom-free success rate, while at a mean of 29 months Thomas-Gibson et al 9 reported only 41% of patients free of symptoms. Morini et al 6 reported that at Ϸ64 months 52.9% of patients had avoided symptomatic recurrence, but this number excludes 9 of the original 43 patients in that study who were technical failures.…”
Section: Summary Of Technique and Outcomesmentioning
confidence: 99%
“…On an "intent to treat" basis, their success rate falls to 42%. Sabate et al 7 reported that 43% of their endoscopically dilated patients needed surgery at 5 years. Roughly speaking, these recurrence rates for endoscopic balloon dilatation are at least double that found after surgery done for stricturing CD.…”
Section: Summary Of Technique and Outcomesmentioning
confidence: 99%